OPTIMIZATION OF BANDUNG CITY’S HUMAN RESOURCE POTENTIAL TO SUPPORT INCLUSIVE URBAN GOVERNANCE - Risna Haryati; Ade Mubarok (CV. Radja Publika, 2026)
This study discusses the optimization of human resource potential in Bandung City to support inclusive urban governance. As one of Indonesia’s major urban centers, Bandung faces various challenges related to public services, social inequality, population growth, digital transformation, and community participation. Human resources are considered a key element in addressing these challenges because they include not only government officials, but also citizens, academics, creative communities, entrepreneurs, and civil society organizations. This study uses a qualitative descriptive method with a literature study approach. The data were collected from books, journal articles, government reports, policy documents, and previous studies related to human resource development, inclusive governance, urban development, smart city implementation, and Bandung City. The data were analyzed descriptively by identifying key themes such as community participation, government capacity, stakeholder collaboration, digital innovation, and public service inclusion. The results show that Bandung City has strong human resource potential, supported by its identity as a city of education, creativity, and innovation. However, this potential needs to be optimized through capacity building, digital literacy improvement, participatory planning, and collaboration among stakeholders. Inclusive urban governance requires the active involvement of all social groups, including women, youth, persons with disabilities, low-income communities, and other vulnerable groups. Therefore, the optimization of human resources is essential to create a governance system that is more responsive, participatory, equitable, and sustainable.